The importance of arabic language in Malaysian tourism industry - Che Mat, Azman; Zakaria, Azman; Jusoff, Kamaruzaman (Canadian Academy of Oriental and Occidental Culture, 2009)
The tourism industry in Malaysia has faced a new trend of Arab tourists’ influx since year 2000. The Arabs spend the highest amount of expenses of RM 5,000.00 per trip. This has given a big benefit for the country’s income. Unfortunately, Malaysia lacks psychological faculties, which is related to the language barriers to cater to Arab needs. The Deputy Tourism Minister has launched a programme to provide Arabic speaking students to serve in five star hotels in the city. This phenomenon clearly indicates a low concern of the tourism industry in providing skilful trainees in the tourism industry in Arabic language and at present there are no Arabic Language courses in tourism programmes to emphasize on the language skills at university level. This paper will try to share the importance of Arabic language skills in tourism industry and tourism program in HLI (Higher Learning Institution). In conclusion, it is hoped that the paper will give some insight to promote courses in Arabic Language Skills for government servants especially the police, customs and others in order to increase their levels of efficiency concerning the language.